RADIOLOGICAL DIAGNOSTIC APPROACHES IN CRYPTORCHIDISM - UTILITY, SENSITIVITY, AND EFFECTIVENESS - Pashoska Vasileska, Milkica; Nikolova, Sonja; Dimitrijevik, Kristina; Ognenoska, Biljana; Panchevska, Ivana (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Objective : This study aims to evaluate the diagnostic accuracy of Diffusion-Weighted Imaging (DWI) in localizing undescended testicles (cryptorchidism) using laparoscopic findings as the gold standard in our local population. Material and Method : Within this study, DW-MRI is employed for localizing undescended testicles, with classic orchidopexy findings serving as the gold standard. Ten patients, six with unilateral undescended testicles and four with bilateral undescended testicles, were included. All patients underwent ultrasound examination, and five were subsequently evaluated with MRI incorporating a diffusion sequence. Results : DWI using magnetic resonance imaging, particularly when performed with a high b value (greater or equal than 3000 s mm-2), enhances the detection of undescended testicles. Diagnostic accuracy consistent with classic orchidopexy findings was achieved in five patients. Conclusion : DW-MRI improves the detection of undescended testes and may serve as the preferred imaging modality to enhance preoperative diagnostic accuracy in localizing non-palpable undescended testicles. Keywords: cryptorchidism, diagnostics, accuracy, MRI-DWI, classical orchidopexy, radiology